2020
DOI: 10.1007/s42452-020-2142-4
|View full text |Cite
|
Sign up to set email alerts
|

The antimicrobial properties of Moringa oleifera Lam. for water treatment: a systematic review

Abstract: Plant extracts have been used as alternatives to the conventional chemical water treatment. Moringa oleifera Lam. is one of the plants used for this purpose due to its antimicrobial and coagulant properties. However, there is no systematization of Moringa's application methodology. Different parts of the plant, extraction methods and concentrations can be applied to remove several pathogens present in contaminated drinking water. In the present work, reported Moringa applications with antimicrobial effect were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 25 publications
(54 reference statements)
3
16
0
Order By: Relevance
“…The antimicrobial activity of the crude extract (MoCE) and heat-treated sample (MoHT15) were evaluated in order to establish whether the powerful papain inhibitor from M. oleifera is able to inhibit bacterial growth. As observed in Table 5, our results confirmed the findings from Bancessi and colleagues [3] that reported a strong antimicrobial activity of Moringa seed extracts against E. coli, E. faecalis, S. aureaus, E. cloacae, Proteus, K. pneumoniae. More interestingly, the heat-treated sample showed a strong inhibitory effect against the growth of E. faecalis and S. aureaus.…”
Section: Antimicrobial Activitysupporting
confidence: 92%
See 1 more Smart Citation
“…The antimicrobial activity of the crude extract (MoCE) and heat-treated sample (MoHT15) were evaluated in order to establish whether the powerful papain inhibitor from M. oleifera is able to inhibit bacterial growth. As observed in Table 5, our results confirmed the findings from Bancessi and colleagues [3] that reported a strong antimicrobial activity of Moringa seed extracts against E. coli, E. faecalis, S. aureaus, E. cloacae, Proteus, K. pneumoniae. More interestingly, the heat-treated sample showed a strong inhibitory effect against the growth of E. faecalis and S. aureaus.…”
Section: Antimicrobial Activitysupporting
confidence: 92%
“…Recent studies have shown that extracts of this plant possess strong antioxidant, anticancer, anti-inflammatory and antidiabetic properties [2]. Furthermore, evidence suggests that almost all parts of the plant exhibit antibacterial activity [3]. In many cases, such antibacterial activity has been associated with the presence of small chemical compounds such as glucosinolates (β-thioglucoside N-hydroxysulfates), isothiocyanates, organic carbamates, chalcone-oxazolidinone hybrids and thiocarbamate [4].…”
Section: Introductionmentioning
confidence: 99%
“…2018; Bancessi et al . 2020). This could explain why there are no standard procedures for the use of M. oleifera in water treatment, despite its widely reported antimicrobial properties (Bancessi et al .…”
Section: Resultsmentioning
confidence: 99%
“…This could explain why there are no standard procedures for the use of M. oleifera in water treatment, despite its widely reported antimicrobial properties (Bancessi et al . 2020). An important result from this study is that a low concentration of M. oleifera was required to reduce the V. cholerae load in the rearing water of shrimp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation